2010
DOI: 10.1099/ijs.0.018051-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudidiomarina aestuarii sp. nov., a marine bacterium isolated from shallow coastal seawater

Abstract: A non-motile, rod-shaped and aerobic marine bacterium, designated strain KYW314 T , was isolated from seawater collected from the South Sea, Republic of Korea. Cells were Gramnegative, catalase-and oxidase-positive and had proteolytic activity. The major fatty acids were iso-C 15 : 0 (17.2 %), C 16 : 0 (11.1 %), iso-C 17 : 0 (10.5 %) and C 18 : 1 v7c (10.0 %). The DNA G+C content was 56.4 mol%. A phylogenetic tree based on 16S rRNA gene sequences showed that strain KYW314 T formed a lineage within the genus Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The enzyme activities detected by the API ZYM system and the carbon sources utilized by strain TS-T11 T and the three reference type strains are specified in both and the species description. Almost all the results obtained in this study for the reference type strains were consistent with those originally described (Jean et al , 2006; Park et al , 2010; Yoon et al , 2007), with the exception of leucine arylamidase and trypsin activity and hydrolysis of gelatin, l -arginine and urea for I. aestuarii JCM 16344 T (Park et al , 2010). These experiments were repeated several times and the same results were obtained, suggesting that these properties may be variable in I. aestuarii .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The enzyme activities detected by the API ZYM system and the carbon sources utilized by strain TS-T11 T and the three reference type strains are specified in both and the species description. Almost all the results obtained in this study for the reference type strains were consistent with those originally described (Jean et al , 2006; Park et al , 2010; Yoon et al , 2007), with the exception of leucine arylamidase and trypsin activity and hydrolysis of gelatin, l -arginine and urea for I. aestuarii JCM 16344 T (Park et al , 2010). These experiments were repeated several times and the same results were obtained, suggesting that these properties may be variable in I. aestuarii .…”
supporting
confidence: 91%
“…The fatty acid profiles of strain TS-T11 T and the three reference type strains are shown in . The cellular fatty acid profiles obtained in this study for the reference type strains were similar to those originally reported (Jean et al , 2006; Park et al , 2010; Yoon et al , 2007) and reported in other publications (Chen et al , 2012; Song et al , 2013; Taborda et al , 2009) in terms of major fatty acids. All these strains contained iso-C 15 : 0 , iso-C 17 : 0 and iso-C 17 : 1 ω9 c as major fatty acids, although in different proportions, which might be due to the different culture conditions.…”
supporting
confidence: 90%
“…The description is identical to that given for Pseudidiomarina aestuarii by Park et al (2010) . Additional characteristics are as follows: the polar lipids comprise PE, PG, DPG, and six uncharacterized PLs (PL1-PL5, PL12); hydrolysis of urea, gelatin, L -arginine, and the enzyme activities of leucine arylamidase and trypsin in API ZYM tests are variable ( Zhong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 65%
“…The major cellular fatty acids present are iso-C 15:0 and iso-C 17:0 (Ivanova et al 2004;Jean et al 2006) and the major isoprenoid quinone is ubiquinone 8 (Q-8) (Taborda et al 2009). Members of the family Idiomarinaceae have been isolated from variety of saline habitats, such as deep sea waters (Ivanova et al 2000), surface sea waters (Brettar et al 2003;Huang et al 2011;Wang et al 2011;Wu et al 2009), submarine hydrothermal fluids (Donachie et al 2003), estuarine waters (Jean et al 2006;Park et al 2010), coastal sediments (Hu and Li 2007), seashore sand (Kwon et al 2006), solar salterns (Taborda et al 2009;Yoon et al 2007) and inland hypersaline wetlands (Martínez-Cánovas et al 2004). The family Idiomarinaceae currently comprises the genera Aliidiomarina and Idiomarina as species originally assigned to the genus Pseudidiomarina were reassigned to the genus Idiomarina by Taborda et al (2009) as these two genera can not be differentiated on the basis of the phenotypic characteristics.…”
Section: Introductionmentioning
confidence: 99%